Plano de proteção de aqüíferos a partir de variáveis ambientais - Dutra, Denecir de Almeida (2005)
The available water reserve, economically viable for the human consumption, only restricts that parcel that if finds in the superficial and groundwater form, that represents only 0.7% of the water fresh existing in the surface of the Land. Like this, the present study it had as objective generality to propose a plan of protection of aquifers for the watershed of the Arroio Ferreira, located in the city of Santa Maria/RS. The specific objectives were to identify the from partner-ambient variables of the watershed, to elaborate plain of information with the use of the technology GIS and to establish the crossing of the information plans, being gotten itself thus zones of aquifers protection. In this way, defined five zones of protection of the aquifers: Zone I - Immediate protection, Zone II - Restriction and control, Zone III - Without restriction, Zone IV - Prevention and Zone V - Direct influence of watercourse, adapted of the norms established for the protection of the wells and areas of aquifers recharge, as well as of previous works. As we could observe the watershed of the Arroio Ferreira presents propitious natural conditions to the contamination of groundwaters, beyond to belong hydrogeology of the Aquifer System Guarani. The generated plans of information with the use of the technology GIS, had assisted for the definitions of the zones of protection of the aquifers. Conclude, therefore that, the preservation of the amount and the quality of the groundwater, as much for this as for the future generations, not only depends on the actions of the professionals of the area, but also of each individual of the society, respecting the restrictions and conditions proposals to the implantation or development of socioeconomic as activities, as well as of the measures of control of the sources of pollution in each zone of protection.